2022
DOI: 10.1021/acs.jmedchem.2c00598
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design of Xanthine-Benzimidazole Derivatives as Novel and Potent Tryptophan Hydroxylase Inhibitors

Abstract: Tryptophan hydroxylases catalyze the first and rate-limiting step in the synthesis of serotonin. Serotonin is a key neurotransmitter in the central nervous system and, in the periphery, functions as a local hormone with multiple physiological functions. Studies in genetically altered mouse models have shown that dysregulation of peripheral serotonin levels leads to metabolic, inflammatory, and fibrotic diseases. Overproduction of serotonin by tumor cells causes severe symptoms typical for the carcinoid syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Moreover, the introduction of electron-withdrawing ( 9 versus 12 , 16 versus 17 , Table and SI Tables S1 and S2) or electron-donating groups ( 9 versus 10 , Table and SI Tables S1 and S2) at substituent R 3 considerably impacts the potency by increasing or decreasing the inhibitory performance, respectively. This shows the significance of electronic properties at the R 3 substituents for inhibitory potency which is similar to our previous findings for the first generation xanthine benzimidazole inhibitor series . Overall, we observed that the more electron-rich the R 3 substituent is, the stronger the chelating interaction between the N 4 atom of the imidazo­[2,1- b ]­thiazoles and the catalytically active iron atom, and the higher the inhibitory potency.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Moreover, the introduction of electron-withdrawing ( 9 versus 12 , 16 versus 17 , Table and SI Tables S1 and S2) or electron-donating groups ( 9 versus 10 , Table and SI Tables S1 and S2) at substituent R 3 considerably impacts the potency by increasing or decreasing the inhibitory performance, respectively. This shows the significance of electronic properties at the R 3 substituents for inhibitory potency which is similar to our previous findings for the first generation xanthine benzimidazole inhibitor series . Overall, we observed that the more electron-rich the R 3 substituent is, the stronger the chelating interaction between the N 4 atom of the imidazo­[2,1- b ]­thiazoles and the catalytically active iron atom, and the higher the inhibitory potency.…”
Section: Resultsmentioning
confidence: 92%
“…They simultaneously occupy, similar to the inhibitor rac- 3 (Figure B), the binding sites of the cosubstrate pterin and the substrate tryptophan, while TPH2 is known to have an approximately 10-fold lower K M value for the cosubstrate pterin compared to TPH1 . Telotristat 1.2 , however, mainly targets the substrate binding site of tryptophan, thus revealing almost identical inhibitory potencies for the two TPH isoforms (Table ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations